1998
DOI: 10.1002/(sici)1097-4636(19981205)42:3<396::aid-jbm7>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Open pore biodegradable matrices formed with gas foaming

Abstract: Engineering tissues utilizing biodegradable polymer matrices is a promising approach to the treatment of a number of diseases. However, processing techniques utilized to fabricate these matrices typically involve organic solvents and/or high temperatures. Here we describe a process for fabricating matrices without the use of organic solvents and/or elevated temperatures. Disks comprised of polymer [e.g., poly (D,L-lactic-co-glycolic acid)] and NaCl particles were compression molded at room temperature and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
336
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 259 publications
(346 citation statements)
references
References 9 publications
6
336
0
4
Order By: Relevance
“…[337][338][339][340][341][342][343] It has been shown that this method allows open-pore structures to be produced, when polymer is preventively mixed with a porogen. [337][338][339][340][341][342][343] Mixture is then equilibrated with high-pressure CO 2 for at least 16 h. [337][338][339][340][341][342][343] Then, by rapidly decreasing pressure (2-to 3-min), CO 2 nucleates and expands, thus causing polymeric particles to fuse. [337][338][339][340][341][342][343] Porogens are successively leached out only for 24 h, to assure removal of salt crystals and retention of entrapped molecule loading.…”
Section: Gas Foamingmentioning
confidence: 99%
See 2 more Smart Citations
“…[337][338][339][340][341][342][343] It has been shown that this method allows open-pore structures to be produced, when polymer is preventively mixed with a porogen. [337][338][339][340][341][342][343] Mixture is then equilibrated with high-pressure CO 2 for at least 16 h. [337][338][339][340][341][342][343] Then, by rapidly decreasing pressure (2-to 3-min), CO 2 nucleates and expands, thus causing polymeric particles to fuse. [337][338][339][340][341][342][343] Porogens are successively leached out only for 24 h, to assure removal of salt crystals and retention of entrapped molecule loading.…”
Section: Gas Foamingmentioning
confidence: 99%
“…[337][338][339][340][341][342][343] Porogens are successively leached out only for 24 h, to assure removal of salt crystals and retention of entrapped molecule loading. [337][338][339][340][341][342][343] It has also been shown that entrapped proteins and plasmid DNAs suffered only a minimal loss in activity. [337][338][339][340][341][342][343] Other gas foaming methods utilize mixtures of effervescent salts as porogens.…”
Section: Gas Foamingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been developed to prepare these kinds of porous three-dimensional biodegradable scaffolds, including gas foaming, [63,64] fiber extrusion and bonding, [65] three-dimensional printing, [66] phase separation, [67 -69] emulsion freeze-drying, [70] and porogen leaching. [71,72] The gas-foaming technique uses high-pressure CO 2 gas processing.…”
Section: Preparation Of Porous Three-dimensional Scaffoldsmentioning
confidence: 99%
“…To improve the pore structure, a combination technique of gas foaming and particulate leaching has been recently proposed. [64] Open-pore biodegradable scaffolds have been fabricated. Disks composed of biodegradable polymer and salt particulates are compression-molded at room temperature and subsequently allowed to equilibrate with high-pressure CO 2 gas.…”
Section: Preparation Of Porous Three-dimensional Scaffoldsmentioning
confidence: 99%